IgE serological tests based on natural house dust mite extracts underestimate allergen-specific IgE levels compared to recombinant allergen-based tests - Huey-Jy Huang; Yvonne Resch-Marat; Kuan-Wei Chen; Renata Kiss; Rudolf Valenta; Susanne Vrtala (Revista Alergia México, 2018)
Background: House dust mites (HDM) are distributed almost worldwide and are the main elicitors of indoor allergies. Diagnosis of HDM allergy is mainly performed with natural allergen extracts which are often of insufficient quality.